Konsep Ketuhanan Agama-agama dan Implikasinya terhadap Dunia Islam - Sumiran, Sumiran; Tamyiz, Achmad; Shodiq, Arsyad; Masruroh, Masruroh; Muzahid, Hizbullah (TSAQOFAH, 2026)
Although the concept of divinity in various religions has been widely studied, research that specifically examines the implications of differing concepts of God for the Islamic worldview as articulated by the ulama salaf and the guidance of the Companions remains limited. This study aims to describe the concept of divinity in major religions, elucidate the fundamental principles of the Islamic worldview, and analyze how these theological differences influence the theological, social, epistemological, and moral dimensions of Islam. Using a qualitative approach with a library research design, data were obtained through the documentation of diverse literature and analyzed using a descriptive-analytical method. The findings indicate that differences in the concept of divinity between Islam and other religions significantly shape an Islamic worldview that is centered on tauhid, positions revelation as the primary source of truth, and directs the orientation of life toward the Hereafter. These results enrich the theoretical development of the Islamic worldview and yield practical implications for education, the strengthening of Islamic creed, and the enhancement of religious literacy amid pluralism and modernity. Furthermore, the study opens avenues for further research on the application of the Islamic worldview in responding to global challenges and advances in scientific knowledge.